Effect of Selenate on Viability and Selenomethionine Accumulation of Chlorella sorokiniana Grown in Batch Culture. (29th January 2014) - Gojkovic, Živan; Vílchez, Carlos; Torronteras, Rafael; Vigara, Javier; Gómez-Jacinto, Veronica; Janzer, Nora; Gómez-Ariza, José-Luis; Márová, Ivana; Garbayo, Ines
Abstract : The aim of this work was to study the effect of Se(+VI) on viability, cell morphology, and selenomethionine accumulation of the green alga Chlorella sorokiniana grown in batch cultures. Culture exposed to sublethal Se concentrations of 40 mg·L −1 (212  μ M) decreased growth rates for about 25% compared to control. A selenate EC50 value of 45 mg·L −1 (238.2  μ M) was determined. Results showed that chlorophyll and carotenoids contents were not affected by Se exposure, while oxygen evolution decreased by half. Ultrastructural studies revealed granular stroma, fingerprint-like appearance of thylakoids which did not compromise cell activity. Unlike control cultures, SDS PAGE electrophoresis of crude extracts from selenate-exposed cell cultures revealed appearance of a protein band identified as 53 kDa Rubisco large subunit of Chlorella sorokiniana, suggesting that selenate affects expression of the corresponding chloroplast gene as this subunit is encoded in the chloroplast DNA. Results revealed that the microalga was able to accumulate up to 140 mg·kg −1 of SeMet in 120 h of cultivation. This paper shows that Chlorella sorokiniana biomass can be enriched in the high value aminoacid SeMet in batch cultures, while keeping photochemical viability and carbon dioxide fixation activity intact, if exposed to suitable sublethal concentrations of Se.